Relationship of Serum D-dimer Levels with Severity of COVID-19 Infection in Term Pregnancy and Prediction of Feto-maternal Outcome - Ferdous, Sarmin; Sultana, Nilufar; Razeeb, Mahbubur Rahman; Samad, Fatema Fairuj (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Aim: To evaluate the value of D-dimer as a biomarker for disease severity in COVID-19 positive pregnant women and prediction of fetomaternal outcome. Methods: This cross-sectional study was conducted in Department of obstetrics & gynaecology, Dhaka Medical College Hospital, among the term pregnancy with symptomatic & positive RT PCR for SARS-CoV-2. Total 100 subjects were selected and allocated into two groups- Group A (Patients with normal D-dimer) and group-B (Patients with raised D-dimer). D–dimer level was detected by standard procedure on the first day of admission by SYSMAX CS-1600 analyser in fibrinogen equivalent unit (FEU) and others investigation were performed. Management was conducted according to hospital protocol. All the information collected in data collection sheet and analyzed using SPSS version-22. Result: In this study mean age of the patient was 24.2 ± 6.5 years. It was showed, 27.0% cases were found to have raised D–dimer where 73.0% were normal level with mean value 2.14µg/ml. It was evident from this study is positive significant association between the D dimer level and severity of COVID-19. Mean value was 0.79 ìg/ml in mild cases, 3.27 ìg/ml in moderate disease and 4.89 ìg/ml in severe disease. Fetomaternal outcome was better in patients with lower D-dimer level. Conclusion: Present data concluded that rising D-dimer can aid in predicting severity of COVID-19 pneumonia and there was a significant positive significant association (r=0.941; p=0.001) between the rising D-dimer and worse fetomaternal outcome. Bangladesh J Obstet Gynaecol, 2025; Vol. 40(1): 5-12